Distribution of soil bacteria involved in C cycling across extensive environmental and pedogenic gradients. (19th January 2023) - Xue, Peipei; Minasny, Budiman; McBratney, Alex; Pino, Vanessa; Fajardo, Mario; Luo, Yu
Abstract: Microorganisms play pivotal roles in soil processes. Metabolically related microorganisms constitute functional groups, and diverse microbial functional groups control nutrient cycling in soils. This study explored environmental (i.e., rainfall, temperature) and soil factors driving the distribution of bacterial functional groups involved in soil carbon (C) cycling in paired natural and agricultural ecosystems. Soil samples were collected at a regional scale covering gradients of temperature and rainfall across two orthogonal transects ( 1000 km) in New South Wales, Australia. Putative functions of bacteria were linked to two soil C fractions: particulate organic carbon (POC) and mineral‐associated organic carbon (MAOC). We found: (i) temperature and rainfall were important drivers of bacterial functional groups, while soil properties, such as pH, soil C and nitrogen (N), also presented significant contributions; (ii) community structure of bacteria involved in C cycling was mainly related to POC content but not to MAOC; (iii) paired sampling showed that agricultural practices had significant impacts on the composition and responses of soil bacterial functional groups. This study demonstrated the environmental regulation (e.g., temperature and rainfall) of soil microbial functional groups at large scales, which was altered by agricultural practices. Highlights: Soil bacteria involved in C cycling were investigated across two 1000 km transects. Temperature and rainfall were important drivers of bacterial functional groups at large scale. Paired sampling showed that agriculture led to a significant shift in bacterial functional groups. Community structure of bacterial functional groups were correlated with soil POC but not MAOC.